The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1953
DOI: 10.1021/ja01116a057
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Racemization of Complex Ions. I. Kinetics of the Dissociation and Racemization of Tris-(1,10-phenanthroline)-nickel(II) and Tris-(2,2'-dipyridyl)nickel (II) Complexes1

Abstract: Mechanism of Racemization of Complex Ions. I. Kinetics of the Dissociation and Racemization of Tris-(1,10-phenanthroline)-nickel(II) and Tris-(2,2 '-dipyridyl)nickel ( ) Complexes1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
0
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 0 publications
4
17
0
1
Order By: Relevance
“…[25,26] Herein, it should be noted that the CD spectrum of the reaction solution was almost silent in the p-p* transition region, [19] indicative of the 1:1 formation of the D and L isomers of [NiA C H T U N G T R E N N U N G (phen) 3 ] 2+ in this reaction. When ethanol was added to the reaction solution, green crystals (4), the color of which is distinct from that of 3, were produced after storing it in a refrigerator for several days.…”
mentioning
confidence: 98%
“…[25,26] Herein, it should be noted that the CD spectrum of the reaction solution was almost silent in the p-p* transition region, [19] indicative of the 1:1 formation of the D and L isomers of [NiA C H T U N G T R E N N U N G (phen) 3 ] 2+ in this reaction. When ethanol was added to the reaction solution, green crystals (4), the color of which is distinct from that of 3, were produced after storing it in a refrigerator for several days.…”
mentioning
confidence: 98%
“…Davies and Dwyer (1) found that there was no change in the rate of racemization upon the addition of an excess of phen and hence postulated an intramolecular mechanism. However, Basolo and co-workers (2) showed that there was, within experimental error, no difference between the rates of dissociation of a phen ligand and racemization in acid solutions. They pointed out that if the dissociated product was either symmetrical or if it quickly racemized, then the rate of racemization should not be affected by the presence of an excess of phen and that it was therefore probable that a dissociative mechanism was correct.…”
Section: Introductionmentioning
confidence: 97%
“…Especially, Fe(II)-bipyridyl complex showed thermo-responsive property by thermal activation of the ligand exchange. 21,22 The obtained polymer hybrids by utilizing Fe(II)-bipyridyl complex are also expected to show thermo-responsive property.…”
mentioning
confidence: 99%
“…In this paper, four kinds of metal (M n+ = Ru 2+ , Fe 2+ , Co 2+ , Ni 2+ ) bipyridyl complexes [20][21][22] were used as cross-linking points to prepare organic gel. It was known that Ru(II)-bipyridyl and Fe(II)-bipyridyl complexes were thermodynamically inert, while Fe(II)-bipyridyl complex and Co(II)-bipyridyl complex were kinetically labile.…”
mentioning
confidence: 99%